Restrukturyzacja przedsiębiorstwa jako instrument przekształceń strategicznych - Nikulina, J.A.; Klepikow, W.A. (Business restructuring as a strategic transformation instrument, 2006)
The paper presents significant limitations of the commonly used theory and practice of restructuring. When restructuring is oriented to streamlining or modernization and is not subject to strategic goals, it is not satisfactory. It is crucial to connect restructuring to the company’s development strategy. This is when restructuring becomes its part and instrument.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s.231-235